SAME-SEX PARTNERS AS HOLDERS OF THE RIGHTS TO BIOMEDICALLY ASSISTED FERTILIZATION - Jović-Prlainović, Olga (Glasnik Advokatske komore Vojvodine, 2020)
In some European legislation same-sex partners are allowed access to appropriate conception procedures of biomedically assisted fertilization. Determining the child`s family status in that case involves relinquishment of traditional framework of maternity and paternity: a child, in other words, may have a mother or father and another parent of the same sex. Analyzing the comparative solutions in this area, it can be concluded that same-sex partners as holders of the right to biomedically assisted fertilization are establishing a new parenting paradigm – parenting as a project.